3‐(3‐Methoxyphenyl)‐6‐(3‐amino‐4‐methoxyphenyl)‐7H‐[1, 2, 4] triazolo [3, 4‐b][1, 3, 4] thiadiazine, a novel tubulin inhibitor, evokes G2/M cell cycle arrest and apoptosis in SGC‐7901 and HeLa cells. Issue 3 (23rd October 2019) - Liu, Zi; Lang, Binyue; Gao, Minghuan; Chang, Xing; Guan, Qi; Xu, Qile; Wu, Di; Li, Zengqiang; Zuo, Daiying; Zhang, Weige; Wu, Yingliang
Abstract: Gastric cancer and cervical cancer are two major malignant tumors that threaten human health. The novel chemotherapeutic drugs are needed urgently to treat gastric cancer and cervical cancer with high anticancer activity and metabolic stability. Previously we have reported the synthesis, characterization and identification of a novel combretastatin A‐4 analog, 3‐(3‐methoxyphenyl)‐6‐(3‐amino‐4‐ methoxyphenyl) ‐7H‐[1, 2, 4]triazolo[3, 4‐b][1, 3, 4] thiadiazine (XSD‐7). In this study, we sought to investigate its anticancer mechanisms in a human gastric cancer cell line (SGC‐7901 cells) and human cervical carcinoma cell line (HeLa cells). The 3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide assay showed that XSD‐7 induced cytotoxicity in SGC‐7901 and HeLa cells with inhibitory concentration 50 values of 0.11 ± 0.03 and 0.12 ± 0.05 µM, respectively. Immunofluorescence studies proved that XSD‐7 inhibited microtubule polymerization during cell division in SGC‐7901 and HeLa cells. Then, these cells were arrested at G2/M cell cycle and subsequently progressed into apoptosis. In further study, mitochondrial membrane potential analysis and Western blot analysis demonstrated that XSD‐7 treatment‐induced SGC‐7901 cell apoptosis via both the mitochondria‐mediated pathway and the death receptor‐mediated pathway. In contrast, XSD‐7 induced apoptosis in HeLa cells mainly via the mitochondria‐mediated pathway. Hence, our data indicate that XSD‐7 exerted antiproliferative activity by disrupting microtubule dynamics, leading to cell cycle arrest, and eventually inducing cell apoptosis. XSD‐7 with novel structure has the potential to be developed for therapeutic treatment of gastric cancer and cervical cancer. Abstract : XSD‐7 is a novel microtubule inhibitor. XSD‐7 exhibits potent anticancer properties in SGC‐7901 and HeLa cells. XSD‐7 induces cell cycle arrest and apoptosis.